2016
DOI: 10.1016/j.profnurs.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Nursing Students for Interprofessional Practice: The Interdisciplinary Curriculum for Oncology Palliative Care Education

Abstract: Interprofessional educational experiences for baccalaureate nursing students are essential to prepare them for interprofessional communication, collaboration, and team work. Nurse educators are ideally positioned to develop and lead such initiatives. The purpose of this article is to describe the development and implementation of an interprofessional education (IPE) project involving students in nursing, medicine, social work, and chaplaincy. The Interdisciplinary Curriculum for Oncology Palliative Care Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 14 publications
1
25
0
3
Order By: Relevance
“…This finding is consistent with another study that posited the development of affective dimension and moral standard in the nurses through reflecting on personal feelings using clinical scenarios [44]. It must be cautioned that the IP content which is either too basic or too advanced would be undesirable as this would create redundancy or frustrations [14]. The scenario in the application exercise and the discussion questions must be carefully designed to engage students to think from a wider perspective.…”
Section: Cultivating Sensitivity To Patient's Needssupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is consistent with another study that posited the development of affective dimension and moral standard in the nurses through reflecting on personal feelings using clinical scenarios [44]. It must be cautioned that the IP content which is either too basic or too advanced would be undesirable as this would create redundancy or frustrations [14]. The scenario in the application exercise and the discussion questions must be carefully designed to engage students to think from a wider perspective.…”
Section: Cultivating Sensitivity To Patient's Needssupporting
confidence: 82%
“…A follow up Cochrane review found it difficult to map out how these activities could inform future planning and IP initiatives [15]. Nevertheless, the best model of IP education is yet to be developed [14]. Some of the educators advocated early introduction of IP concept in the curriculum [23], while others implemented IP components when the students gained substantial experiences [14] [24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies reported postgraduate level IPE programs on children palliative care, [ 38 ] dental care, [ 32 , 45 , 47 ] social work, [ 26 , 54 ] and gerontology. [ 36 , 64 ] Undergraduate-level IPE programs emphasized the interdisciplinary collaboration, professionals in health care and team work, [ 18 ] dental care, [ 33 , 36 ] crisis management, [ 70 ] palliative oncology care, [ 19 ] ethics and professionalism training, [ 60 ] and psychosocial oncology practice and research. [ 19 ] Undergraduate-level IPE programs were the basic academic programs which were designed to provide IPE and IPCP training.…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 , 64 ] Undergraduate-level IPE programs emphasized the interdisciplinary collaboration, professionals in health care and team work, [ 18 ] dental care, [ 33 , 36 ] crisis management, [ 70 ] palliative oncology care, [ 19 ] ethics and professionalism training, [ 60 ] and psychosocial oncology practice and research. [ 19 ] Undergraduate-level IPE programs were the basic academic programs which were designed to provide IPE and IPCP training. Most of the IPE programs were conducted as workshops and training within the health care education curricula.…”
Section: Resultsmentioning
confidence: 99%